New Directions in Catholic Historical Research: Saints in Social Work. (2nd October 2017) - Davis, Thomas
ABSTRACT: For over half a century now, the profession of social work has ignored calls to develop critical infrastructures for strengthening and expanding historical research in schools of social work. Since World War II, for example, doctoral dissertations involving significant historical research in schools of social work have become virtually extinct. The vanishing of these dissertations represents a simultaneous vanishing of social work's capacity to detect historical figures who are indigenous to and yet have remained undetected in social work history. As a result, and unintentionally, social work scholars have been seemingly unable to detect Louise de Marillac as the patron saint of social workers or Ellen Gates Starr as a popular folk saint among social workers in Catholic religious orders. The study includes the rare, post-mortem photograph of Ellen Gates Starr, dressed in the full habit of a Catholic Benedictine nun.